Logistics clusters, including inter-firm relations through community detection - Beckers, Joris; Thomas, Isabelle; Vanoutrive, Thomas; Verhetsel, Ann (European Journal of Transport and Infrastructure Research, 2018)
This paper studies clusters in the logistics sector. Like traditional cluster research, indicators of concentration to detect co-location of employment are calculated. However, this approach is enhanced by including a quantitative analysis of the inter-firm relations between logistics companies through the use of a community detection algorithm on a microeconomic dataset of buyer-supplier relations. Combining both results in a typology of logistics clusters. Next to the big clusters characterized by employment concentration and many internal and external relations, spill-over and polycentric clusters are identified. This approach seems promising to detect in future research clusters in other sectors and places